The COVID-19 pandemic and the human rights of persons with mental and cognitive impairments subject to coercive powers in Australia. (November 2020) - Wilson, Kay
Abstract: The purpose of this paper is to explore the effect of the COVID-19 pandemic on the human rights of persons with mental and cognitive impairments subject to coercive powers in Australia. It sets out the relevant human rights in the Convention on the Rights of Persons with Disabilities which have been engaged by the COVID-19 pandemic and the government's response to it. It examines the effect of emergency legislation on the relaxation of human rights safeguards in mental health laws, with a focus on mental health tribunals (although it is limited by a lack of published decisions and gaps in publicly available information). However, some of the issues created for persons with disabilities during the COVID-19 pandemic are evident in some decisions published by the New South Wales Guardianship Tribunal. The paper critically analyses two guardianship decisions UZX [2020] NSWCATGD 3 (3 April, 2020) and GZK [2020] NSWCATGD 5 (23 April, 2020) and some emergency South Australian legislation COVID-19 Emergency Response Act, 2020 (SA) Schedule 1 to demonstrate the ways in which the human rights of persons with mental and cognitive impairments can be more at risk than those of the general population, even when the general population is itself in "lockdown."